The role of systemic inflammatory biomarkers to predict mortality in chronic obstructive pulmonary disease. (February 2013) - Kelly, Emer; Owen, Caroline A; Pinto-Plata, Victor; Celli, Bartolome R
The authors discuss the role of inflammatory biomarkers to predict mortality in chronic obstructive pulmonary disease (COPD) in this narrative literature review with expert opinion. The severity of COPD has traditionally been graded using the degree of obstruction as measured by the forced expiratory volume in 1 s because this variable has been predictive of outcomes. However, it is now accepted that COPD is a complex disease with important systemic consequences and that a multidimensional index such as the BMI, obstruction, dyspnea and exercise capacity index is a better predictor of outcome than lung function alone. Because inflammation is thought to play a pivotal role in the genesis of COPD, several serum inflammatory biomarkers have been investigated. Of the ones studied, C-reactive protein, IL-6, pulmonary and activation-regulated chemokine and fibronectin:C-reactive protein ratio have been observed to be independently associated with increased risk of death. When added to known clinical variables such as the BMI, obstruction, dyspnea and exercise capacity index, only IL-6 has been shown to further contribute to mortality prediction. It is likely that the use of an integrative approach combining biomarkers investigated through high-output technology with clinical parameters, combined with new information from the fields of genomics, transcriptomics, proteomics and metabolomics, will improve the authors capacity to predict mortality in COPD.